Development of in vitro methods to model the impact of vaginal lactobacilli on Staphylococcus aureus biofilm formation on menstrual cups as well as validation of recommended cleaning directions - Friberg, Maria; Woeller, Kara; Iberi, Vighter; Mancheno, Paolo Palacio; Riedeman, James; Bohman, Lisa; Davis, Catherine C. (Frontiers in Reproductive Health, 2023)
Introduction Menstrual cups (MC) are a reusable feminine hygiene product. A recent publication suggested that Staphylococcus aureus (S. aureus) biofilms can form on MCs which may lead to increased risk of menstrual Toxic Shock Syndrome (mTSS). Additionally, there is concern that buildup of residual menses may contribute to microbial growth and biofilm formation further increasing mTSS risk. Quantitative and qualitative analysis of in vitro tests were utilized to determine if S. aureus biofilm could form on MC in the presence of the keystone species Lactobacillus after 12 h of incubation. The methodology was based on a modification of an anaerobic in vitro method that harnesses the keystone species hypothesis by including a representative of vaginal lactic acid bacteria. Methods MCs were incubated anaerobically for 12 h in Vaginal Defined Media (VDM) with the two morphologically distinct bacteria, Lactobacillus gasseri (L. gasseri) and S. aureus. Colony Forming Units (CFU) for each organism from the VDM broth and sonicated MC were estimated. In addition, a separate experiment was conducted where S. aureus was grown for 12 h in the absence of L. gasseri. Qualitative analysis for biofilm formation utilized micro-CT (µ-CT) and cryogenic scanning electron microscopy (Cryo-SEM). Results Samples collected from the media control had expected growth of both organisms after 12 h of incubation. Samples collected from VDM broth were similar to media control at the end of the 12-h study. Total S. aureus cell density on MC following sonication/rinsing was minimal. Results when using a monoculture of S. aureus demonstrated that there was a significant growth of the organism in the media control and broth as well as the sonicated cups indicating that the presence of L. gasseri was important for controlling growth and adherence of S. aureus. Few rod-shaped bacteria (L. gasseri) and cocci (S. aureus) could be identified on the MCs when grown in a dual species culture inoculum and no biofilm was noted via µ-CT and cryo-SEM. Additionally, efforts to model and understand the validity of the current labeled recommendations for MC cleaning in-between uses are supported. Discussion The data support continued safe use of the Tampax® cup when used and maintained as recommended.